Concentration of Particulate Matter and Air Humidity in Pediatric Intensive Care Unit - Pasaribu Hotber Edwin Rolan; Afandi Dedi; Hamidy Yulis (E3S Web of Conferences)
Human activities are predominantly conducted indoors, making it equally important to ensure good indoor air quality as it is to maintain outdoor air quality. The quality of indoor air is partly determined by the levels of PM2.5 (particles with an aerodynamic diameter ≤2.5μ m) and PM10 (particles with an aerodynamic diameter d ≤10 μm) and humidity. The Pediatric Intensive Care Unit (PICU) is a space that must maintain high air quality because it is continuously occupied by pediatric patients and healthcare personnel 24 hours a day, 7 days a week. In this study, the indoor air quality in the PICU Arifin Achmad General Hospital (AAGH) in Riau Province, Indonesia, was observed using a descriptive observational study with a longitudinal and time-series design. The results of this study demonstrated that the PM2.5 levels decreased from 9.25 µg/m³ in the morning to 3.3 µg/m³ in the afternoon, whereas PM10 levels decreased from 17.7 µg/m³ in the morning to 7.8 µg/m³ in the afternoon. Additionally, the air humidity increased from 60.7% in the morning to 61.4% in the afternoon. In conclusion, the observations from this study indicated an increase in air humidity from morning to afternoon and the normal particulate matter levels.